Experimental Study on the Flow Behavior of Grout Used in Horizontal Directional Drilling Borehole Grouting to Seal Mining-Induced Overburden Fractures - Jinfeng Ju; Jialin Xu; Jing Yang (Geofluids)
The development of water-conducting fractures from underground coal mining is a geological cause of groundwater loss. Sealing mining-induced rock fracture channels through borehole grouting is an effective way to protect groundwater resources. A ground-based engineering test was conducted at the Gaojiabao coal mine that utilized horizontal directional drilling (HDD) to grout and seal water-conducting overburden fractures. This study carried out a theoretical and experimental exploration using HDD to evaluate the development characteristics and grout hydraulic conductivity of these mining-induced fractures. The results showed that, as a result of varying fracture morphologies in different zones of the mining overburden, multiple fracture types were sequentially exposed as the HDD borehole advanced from the original rock mass outside the mining area towards the mining-induced fractured rock mass. The fracture types were exposed in the following order: compressive shear fractures, tensile failure fractures, and bed separation fractures. Moreover, the void characteristics of the exposed fractures in the borehole were significantly different at different drilling horizons, which affected the flow behavior and sealing performance of the injected grout. Lastly, three typical orders in which the different types of fractures were sequentially exposed by the borehole were summarized, and further analysis of the orders led to a scheme for determining drilling horizons favorable for efficient fracture sealing. The results of this study will enable efficient grout sealing of the fractures caused by mining and reduce groundwater loss.